Suppression of microtubule acetylation mediates the anti-leukemic effect of CDK9 inhibition - Xi Xie; Baoyuan Zhang; Donghe Li; Jiaming Gao; Jiaoyang Li; Chenxuan Liu; Yuqing Dan; Pengfei Xu; Lei Yan; Xu Huang; Rui Zhang; Yunying Yao; et al. (Cancer Cell International)
Abstract Cyclin-dependent kinase 9 (CDK9) is a crucial component of transcription and potential target for anti-cancer therapies, particularly for hematological malignancies. However, the precise mechanisms underlying the therapeutic effects of CDK9 inhibitors remain not fully understood. Here, we found that inhibiting CDK9 either pharmacologically or through gene downregulation, significantly reduced the levels of α-tubulin protein in a time- and dose-dependent manner. We further discovered that CDK9 inhibition led to increased susceptibility of α-tubulin to proteasomal degradation due to reduced acetylation at lysine 40 (K40), an important modification for microtubule stability. An acetylation-mimicking mutant of α-tubulin mitigated the anti-tumor effects of CDK9 inhibition. Mechanically, we identified that CDK9 inhibition downregulated the expression of ATAT1, the acetyltransferase responsible for α-tubulin acetylation, further compromising microtubule stability. We also conducted in vivo studies in a leukemic xenograft model, where AZD4573 treatment led to significant tumor regression, decreased ATAT1 expression, and α-tubulin degradation. Our study unravels a novel molecular mechanism by which CDK9 inhibition disrupts α-tubulin stability and provides valuable insights for exploring effective treatment regimens involving CDK9 inhibitors.